Gray matter differences in patients with functional movement disorders. (13th November 2018) - Maurer, Carine W.; LaFaver, Kathrin; Limachia, Gaurang S.; Capitan, Geanna; Ameli, Rezvan; Sinclair, Stephen; Epstein, Steven A.; Hallett, Mark; Horovitz, Silvina G.
Abstract : Objective: To explore alterations in gray matter volume in patients with functional movement disorders. Methods: We obtained T1-weighted MRI on 48 patients with clinically definite functional movement disorders, a subset of functional neurologic symptom disorder characterized by abnormal involuntary movements, and on 55 age- and sex-matched healthy controls. We compared between-group differences in gray matter volume using voxel-based morphometry across the whole brain. All participants in addition underwent a thorough neuropsychological battery, including the Hamilton Anxiety and Depression Scales and the Childhood Trauma Questionnaire. To determine whether confounding factors such as comorbid depression, anxiety, or childhood trauma exposure contributed to the observed structural changes, nonparametric correlation analysis was performed. Results: Patients with functional movement disorders exhibited increased volume of the left amygdala, left striatum, left cerebellum, left fusiform gyrus, and bilateral thalamus, and decreased volume of the left sensorimotor cortex (whole-brain corrected p ⩽ 0.05). Volumetric differences did not correlate with measures of disease duration or patient-rated disease severity. Conclusion: This study demonstrates that patients with functional movement disorders exhibit structural gray matter abnormalities in critical components of the limbic and sensorimotor circuitry. These abnormalities may represent a premorbid trait rendering patients more susceptible to disease, the disease itself, or a compensatory response to disease.